If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 24 + -3(2x + 1) Reorder the terms: x = 24 + -3(1 + 2x) x = 24 + (1 * -3 + 2x * -3) x = 24 + (-3 + -6x) Combine like terms: 24 + -3 = 21 x = 21 + -6x Solving x = 21 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. x + 6x = 21 + -6x + 6x Combine like terms: x + 6x = 7x 7x = 21 + -6x + 6x Combine like terms: -6x + 6x = 0 7x = 21 + 0 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 3f-9=14f+1 | | 8y-20=4y | | (x)(2+3x)=320 | | h(n-4)=-3n-4 | | 13m+4w=1223 | | x/12-18=31 | | 60+20m=720 | | 2x^2+2y^2-4x+4y+18=O | | 6(-7p-8)=-90 | | 3.2x-15=4x | | -3x=-5x+2(7+2) | | 17v+v-16v=20 | | 1+6(7p-7)=-335 | | 33-8p=-527 | | x^2+2x-3=129 | | -6z+3=3-z | | 17r-15r-2r+r=13 | | 17z+z-17z=14 | | (2x-10)=(x+25) | | .25(y+1)=2y-4(y-4) | | 20+2y+20=-8y-20 | | 7=-14 | | 7=-14b | | x^2y^2z^2/xyz | | x+6k=0 | | 34a-32a+8=96 | | 6(5^10)/3(5^8) | | -48=6s | | 4/5x^0 | | 7x-6x=90 | | 8s+2s+12-3s-10+-2-6s= | | 10+6z=3z-8 |